2011
DOI: 10.5688/ajpe75462
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Scaffolding to Improve Students’ Skills in Evaluating Clinical Literature

Abstract: Objective. To implement and assess the effectiveness of an activity to teach pharmacy students to critically evaluate clinical literature using instructional scaffolding and a Clinical Trial Evaluation Rubric. Design. The literature evaluation activity centered on a single clinical research article and involved individual, small group, and large group instruction, with carefully structured, evidence-based scaffolds and support materials centered around 3 educational themes: (1) the reader's awareness of text o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…28 This is similar to the concept of scaffolding, a metaphor for providing learning support, such as clinical algorithms, during teaching as one provides a physical scaffold around a building under construction, and which addresses the learning of concepts and metacognitive skills. 29,30 Several studies have described the use of instructional scaffolds as structured approaches to facilitate learning. 29,31 It is likely that peer teaching also contributed to the effectiveness of this educational opportunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 This is similar to the concept of scaffolding, a metaphor for providing learning support, such as clinical algorithms, during teaching as one provides a physical scaffold around a building under construction, and which addresses the learning of concepts and metacognitive skills. 29,30 Several studies have described the use of instructional scaffolds as structured approaches to facilitate learning. 29,31 It is likely that peer teaching also contributed to the effectiveness of this educational opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Several studies have described the use of instructional scaffolds as structured approaches to facilitate learning. 29,31 It is likely that peer teaching also contributed to the effectiveness of this educational opportunity. One possible consequence of specialists teaching family physicians about dementia is the unspoken message that only specialists can effectively manage dementia, leaving physicians more knowledgeable, but hesitant to tackle such a complex topic without referral.…”
Section: Discussionmentioning
confidence: 99%
“…6,[9][10][11] Particularly in Japan where EBM skills are In contrast, in the US school surveyed, where EBM training and presentations are required throughout the didactic courses and experiential education, all environmental barriers were identified by <50% of American students, yet EBM use is still suboptimal. Although several studies showed the effectiveness of EBM training in increasing knowledge in students and practitioners with various methods, including a brief one day workshop, journal club, monograph assignment, and computer-or lecture-based instructions, [29][30][31][32][33][34] knowledge of EBM does not equate to their actual usage of EBM. Some studies have shown no changes in clinician behavior to use EBM even though training improved their knowledge and skills.…”
Section: -24mentioning
confidence: 99%
“…33 ( [28][29][30][31][32][33][34][35][36] However, only one study examined the impact of a longitudinal EBM curriculum, and we previously reported our experience with integrating EBM into a didactic pharmacoeconomics course assignment. 37,38 Because little is known about the attitudes and perceptions of student pharmacists towards EBM, our objective was to describe our longitudinal EBM curriculum and to evaluate these aspects among student pharmacists after exposure to an EBM course that uses interactive pedagogical methods, along with a longitudinal EBM curriculum.…”
Section: A J P Ementioning
confidence: 99%